Bending Strengths of Large-leaf Mahogany (Swietenia macrophylla King) and Mangium (Acacia mangium Willd) Commercial Lumbers in Northeastern Mindanao, Philippines - Cossid, Rey Naldoza; Torralba, Jan Michael Ampong; Clemente, John Harold Merantes; Villaflor, Chary Joyce Gabriel; Jandug, Catherine Mhae Buctuan; Casilac Jr, Cornelio Sacquiap (Jurnal Sylva Lestari, 2025)
Large-leaf mahogany (Swietenia macrophylla King) and mangium (Acacia mangium Willd) have been the preferred wood for furniture and cabinets for ages. S. macrophylla is famous around the world for the wood it provides. This study investigated the bending strength (modulus of rupture (MOR) and modulus of elasticity (MOE)) of S. macrophylla and A. mangium commercially available lumbers sold at roadside lumber dealers in northeastern Mindanao (Provinces of Agusan del Norte, Agusan del Sur and Misamis Oriental), Philippines. Four lumbers were acquired for each species in every province. A total of 12 lumbers per species were collected from the three provinces, or 24 sampled lumbers. These lumbers were further processed into a nominal dimension of 1.5 cm × 1.5 cm × 27.6 cm. All samples were oven-dried at 105 ± 3°C for 24 hours inside a laboratory oven until no more moisture could be removed. The 3-point test jig was fabricated and adapted to a kidizen science-free design but modified for this study. The results show no significant differences in bending strength at a 0.01 significance level among the three provinces and between species. Overall, bending strength is comparable across provinces and species. For S. macrophylla and A. mangium, Agusan del Norte obtained the highest MOR and MOE (54.707 MPa, 63.002 MPa). The MOE of S. macrophylla in Agusan del Norte was also high (6,825 MPa), but for A. mangium, Misamis Oriental province was the highest. Keywords: 3-point test jig, load deflection, mahogany, modulus of elasticity, modulus of rupture